2001
DOI: 10.1159/000050574
|View full text |Cite
|
Sign up to set email alerts
|

Daytime Pulmonary Hypertension in Patients with Obstructive Sleep Apnea

Abstract: Background: Limited information exists regarding the development of pulmonary hypertension in patients with obstructive sleep apnea (OSA) in the absence of lung and heart comorbidity. Objectives: The aims of this study were to investigate whether OSA patients without any other cardiac or lung disease develop pulmonary hypertension, and to assess the effect of continuous positive airway pressure (CPAP) treatment on pulmonary artery pressure (PPA). Methods: Twenty-nine patients aged 51 ± 10 years with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
2
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(35 citation statements)
references
References 15 publications
1
27
2
4
Order By: Relevance
“…Notwhitstanding, the prevalence for PH in the OSAS group (Group-3) was higher than that reported for other European populations with OSAS (17-27%) living at an altitude, on average, 150 m above sea level 4,7,8,13,14 and with mean BMI between 31 and 35, except for the report of Alchanatis et al 13 in which the BMI of the patients was in the lower limit of our sample (4177).…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Notwhitstanding, the prevalence for PH in the OSAS group (Group-3) was higher than that reported for other European populations with OSAS (17-27%) living at an altitude, on average, 150 m above sea level 4,7,8,13,14 and with mean BMI between 31 and 35, except for the report of Alchanatis et al 13 in which the BMI of the patients was in the lower limit of our sample (4177).…”
Section: Discussioncontrasting
confidence: 82%
“…For example, Sajkov et al 20 showed a correlation of r ¼ 0.96, Po0.001 between catheter-measured and Doppler estimates. More recently, Alchanatis et al 13 had shown similar correlation. The echocardiographic measurements were carried out by a single, experienced, trained specialist while the patient was awake, in left lateral decubitus position with a 201 upper body tilt, in the morning 30-60 min after the second night of polysomnography.…”
Section: Study Design and Polysomnography (Psg)mentioning
confidence: 67%
See 1 more Smart Citation
“…Some authors [29]showed that OSAS was an independent risk factor leading to PH, whereas others [8]indicated that daytime hypoxemia was necessary to develop persistent PH. In our study nocturnal hypoxemia was observed in subjects with OSAS and not in mostly mild or moderate COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Most experts feel that OSA may modestly increase pulmonary arterial pressures, and evaluation for OSA should be part of the initial work-up in patients with pulmonary hypertension [84]. Therapy with CPAP has been shown to decrease pulmonary pressures in OSA patients with either high or normal pulmonary pressures [84, 85]. …”
Section: Right Ventricle Pulmonary Hypertension and Osamentioning
confidence: 99%